Comparison between universal molecular screening for Lynch syndrome and revised Bethesda guidelines in a large population-based cohort of patients with colorectal cancer. Issue 6 (25th August 2011) - Pérez-Carbonell, Lucía; Ruiz-Ponte, Clara; Guarinos, Carla; Alenda, Cristina; Payá, Artemio; Brea, Alejandro; Egoavil, Cecilia M; Castillejo, Adela; Barberá, Victor M; Bessa, Xavier; Xicola, Rosa M; Rodríguez-Soler, María; et al.
Abstract : Background: The selection of patients for genetic testing to rule out Lynch syndrome is currently based on fulfilment of at least one of the revised Bethesda criteria followed by mismatch repair (MMR) status analysis. A study was undertaken to compare the present approach with universal MMR study-based strategies to detect Lynch syndrome in a large series of patients with colorectal cancer (CRC). Methods: 2093 patients with CRC from the EPICOLON I and II cohorts were included. Immunohistochemistry for MMR proteins and/or microsatellite instability (MSI) analysis was performed in tumour tissue. Germline MLH1 and MSH2 mutation analysis was performed in patients whose tumours showed loss of MLH1 or MSH2 staining, respectively. MSH6 genetic testing was done in patients whose tumours showed lack of MSH6 expression or a combined lack of MSH2 and MSH6 expression but did not have MSH2 mutations. PMS2 genetic testing was performed in patients showing isolated loss of PMS2 expression. In patients with MSI tumours and normal or not available MMR protein expression, all four MMR genes were studied. Results: A total of 180 patients (8.6%) showed loss of expression of some of the MMR proteins and/or MSI. Four hundred and eighty-six patients (23.2%) met some of the revised Bethesda criteria. Of the 14 (0.7%) patients who had a MMR gene mutation, 12 fulfilled at least one of the revised Bethesda criteria and two (14.3%) did not. Conclusions: Routine molecular screening of patients with CRC for Lynch syndrome using immunohistochemistry or MSI has better sensitivity for detecting mutation carriers than the Bethesda guidelines.